Nutritional Status in Children with Congenital Heart Disease: Prevalence and Its Associated Factors - Rafner lndra; Tina Christina L Tobing; Ahmad Dian Siregar; Abdullah Afif Siregar; Endang D Hamid; Iskandar Z Lubis (Indonesian Pediatric Society, 1998)
A cross sectional study was undertaken on 58 children (age range 4 months-15 years) With congenital heart disease (CHD) and in controls of 58 subjects without CHD. The study was performed by anthropometric examination, history of acute respiratory tract infection, dietary intake, simple laboratory examination and type and severity of CHD were recorded. There were significant differences in: 1. Nutritional status between patients With CHD and without CHD (p<0.001). 2. Frequency of acute respiratory tract infection between patients with CHD and without CHD (p<0.001). 3. Duration of each episode of acute respiratory tract infection between patients with CHD and without CHD (p<0.05). 4. Calorie and protein intakes between patients with CHD and without CHD (p<0.005). Type of CHD (cyanotic and non-cyanotic) was significantly associated with nutritional status based on height for age among patients with CHD (p<0.01). However, there was no siignificant association between the presence or absence of heart failure with nutritional status among patients with CHD. In conclusion, there were Significantly differences of nutritional status, frequency/duration of acute respiratory tract infection, calories and protein intake between patients with CHD and without CHD. Type of CHD (cyanotic and non-cyanotic) was significantly associated with nutritional status based on height for age.